2022
DOI: 10.3390/nu14193955
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-Oxide Promotes Osteoclast Differentiation and Bone Loss via Activating ROS-Dependent NF-κB Signaling Pathway

Abstract: Trimethylamine-N-oxide (TMAO), an important gut microbiota (GM)-derived metabolite, has been shown to be abnormally increased in osteoporosis. However, the role and underlying mechanism of TMAO in regulating bone loss during osteoporosis have not been fully investigated. In the current study, we found that 100–400 μM TMAO dose-dependently enhanced TRAP-positive osteoclasts, F-actin ring formation, and resorption area on bovine bone slices and up-regulated osteoclast-related gene expression (Calcr, Traf6, Dcsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…89,90 TMAO is abnormally increased during OP progression and contributes to OC differentiation by activating the ROS-dependent NF-κB signaling pathway, thereby resulting in bone loss. 26 In our study, we observed that MLT treatment markedly increased SCFA abundances and partially reduced the production of TMAO-related metabolites, which were consistent with the alteration of gut microbiota. Additionally, a striking finding is that Allobaculum and nearly all kinds of SCFAs exhibited a markedly positive correlation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…89,90 TMAO is abnormally increased during OP progression and contributes to OC differentiation by activating the ROS-dependent NF-κB signaling pathway, thereby resulting in bone loss. 26 In our study, we observed that MLT treatment markedly increased SCFA abundances and partially reduced the production of TMAO-related metabolites, which were consistent with the alteration of gut microbiota. Additionally, a striking finding is that Allobaculum and nearly all kinds of SCFAs exhibited a markedly positive correlation.…”
Section: Discussionsupporting
confidence: 84%
“…21 In addition, TMAO, the gut microbial metabolite of choline, promotes OC differentiation by activating the ROSdependent NF-κB signaling pathway. 26 Notably, common studies have long held that products of microbial aminoacid metabolism possess a deleterious effect on the host, which results in the lack of attention paid to their roles in OP. Emerging evidence suggests that tryptophan metabolism plays a central role in microbiota-host crosstalk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the intestinal microflora are related to many diseases that lead to bone loss, including malnutrition, IBD, obesity, and metabolic disease (Guss et al, 2017). Animal experiments demonstrated that TMAO activates the ROS-dependent NF-kB signaling pathway to enhance osteoclast polarization and cause bone loss in mice (Li et al, 2019;Wang et al, 2022a). Additionally, TMAO can induce impaired intestinal barrier function, resulting in elevated levels of IL-1b and TGF-b (Nanto-Hara et al, 2020;Li et al, 2021b;Xie et al, 2022;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…ROS is the main type of free radical involved in the destruction of bone remodeling 5 . ROS inhibits the expression of Runt‐related transcription factor‐2 (Runx2) and osterix, reducing osteogenic activity, while promoting the expression of osteoclast markers such as C‐Fos, Nuclear Factor of Activated T cells‐1 (NFATc1), and Tartrate Resistant Acid Phosphatase (TRAP) 6,7 . ROS may enhance the response of osteoclast precursors to Receptor Activator of NF‐κB Ligand (RANKL), and induce the production of additional osteoclastic factors, such as IL‐1, IL‐6, and IL‐7 8,9 .…”
Section: Introductionmentioning
confidence: 99%